The legal macroscope: Experimenting with visual legal analytics. (October 2017) - Lettieri, Nicola; Altamura, Antonio; Malandrino, Delfina
This work presents Knowlex, a web application designed for visualization, exploration, and analysis of legal documents coming from different sources. Understanding the legal framework relating to a given issue often requires the analysis of complex legal corpora. When a legal professional or a citizen tries to understand how a given phenomenon is disciplined, his attention cannot be limited to a single source of law but has to be directed on the bigger picture resulting from all the legal sources related to the theme under investigation. Knowlex exploits data visualization to support this activity by means of interactive maps making sense out of heterogeneous documents (norms, case law, legal literature, etc.). Starting from a legislative measure (what we define as Root) given as input by the user, the application implements two visual analytics functionalities aiming to offer new insights on the legal corpus under investigation. The first one is an interactive node graph depicting relations and properties of the documents. The second one is a zoomable treemap showing the topics, the evolution, and the dimension of the legal literature settled over the years around the norm of interest. The article gives an overview of the research so far conducted presenting the results of a preliminary evaluation study aiming at evaluating the effectiveness of visualization in supporting legal activities as well as the effectiveness of Knowlex, the usability of the proposed system, and the overall user satisfaction when interacting with its applications.